2019
DOI: 10.1097/cm9.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin LL-37 restoring glucocorticoid function in smoking and lipopolysaccharide-induced airway inflammation in rats

Abstract: BackgroundGlucocorticoids have been widely used to treat patients with chronic obstructive pulmonary disease (COPD). Nevertheless, corticosteroid insensitivity is a major barrier to the effective treatment of COPD and its mechanism remains unclear. This study aimed to evaluate the effect of cathelicidin LL-37 on corticosteroid insensitivity in COPD rat model, and to explore the involved mechanisms.MethodsCOPD model was established by exposing male Wistar rats to cigarette smoke combined with intratracheal inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Three papers (n = 3/34, 9%) evaluated the interplay between cathelicidin and commonly used COPD and asthma drugs: corticosteroids [ 54 , 55 , 56 ]. Van der Berge et al found no difference in CAMP/LL-37 gene expression between budesonide and fluticasone propionate treatment [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three papers (n = 3/34, 9%) evaluated the interplay between cathelicidin and commonly used COPD and asthma drugs: corticosteroids [ 54 , 55 , 56 ]. Van der Berge et al found no difference in CAMP/LL-37 gene expression between budesonide and fluticasone propionate treatment [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Non-typeable Haemophilus influenzae exacerbates COPD by upregulating PI3K signalling [123][124][125]. It appears that bacterial lipopolysaccharide plays an important role by inducing ROS and a cascade of PI3K signalling in the lung [126][127][128][129]. In addition to bacteria, certain fungi exacerbate the COPD phenotype.…”
Section: Involvement Of Mirnas Targeting Pi3k Signalling In Copd Path...mentioning
confidence: 99%
“…They exposed the whole rats to SCS (tar content 13 mg, and the nicotine content 0.8 mg) for 28 days in a custom-built fumigation chamber of 72L, with an intratracheal injection of LPS on the 1 st and 14 th day. They found increased levels of 8-iso-PGF2α, interleukin-8 (IL-8), and TNF-α in BALF and serum, while a decreased expression level of HDAC2 (histone deacetylase subtype plays a major role in preventing pathogenesis by inhibiting the expression of an inflammatory gene), and increased levels of PI3K, and p-AKT (oxidative stress activates this pathway which ultimately causes phosphorylation and inactivation of HDAC2) in lung tissue [36,37]. Male, Dunkin Hartley out-bred guinea pigs (350-400g) were used in a study for the induction of COPD using 200µl LPS intranasal instillation (5mg/ml in sterile saline).…”
Section: Laboratory Animal Models For Inducing Copd Using Different Ways Of Cs Exposurementioning
confidence: 99%
“…But due to short modelling time, partial COPD characteristics were established. [36,37] Mainstream CS and LPS Rat 24 cigarettes per day 1 h twice a day, 7 days a week, CS (6 week), LPS+CS (4week), CS+LPS (6 week).…”
Section: Use Of Mainstream Cs (Mcs) With Lps For Inducing Copdmentioning
confidence: 99%
See 1 more Smart Citation